Acute stressors do not impair short-term memory or attention in an aged mouse model of amyloidosis - DiMarco, Giuliana M.; Harris, Breanna N.; Savonenko, Alena V.; Soto, Paul L. (Frontiers in Behavioral Neuroscience, 2023)
Memory impairment in Alzheimer’s disease patients is thought to be associated with the accumulation of amyloid-beta peptides and tau proteins. However, inconsistent reports of cognitive deficits in pre-clinical studies have raised questions about the link between amyloid-beta and cognitive decline. One possible explanation may be that studies reporting memory deficits often involve behavioral assessments that entail a high stress component. In contrast, in tasks without a high stress component transgenic mice do not consistently show declines in memory. The glucocorticoid cascade hypothesis of aging and the vicious cycle of stress framework suggest that stress exacerbates dementia progression by initiating a cycle of hypothalamic-pituitary-adrenal axis activation and subsequent brain deterioration. Using the APPswe/PS1dE9 mouse model of amyloidosis, we assessed whether stressor exposure prior to testing differentially impaired cognitive performance of aged male and female mice. As part of a larger study, mice performed a delayed match-to-position (DMTP) or a 3-choice serial-reaction time (3CSRT) task. Unexpectedly, these mice did not exhibit cognitive declines during aging (Soto et al., 2023). At 73 and 74 weeks of age, we exposed mice to a predator odor or forced swim stressor prior to testing to determine if stress revealed cognitive deficits. We predicted stressor exposure would decrease performance accuracy more robustly in transgenic vs. non-transgenic mice. Acute stressor exposure increased accuracy in the DMTP task, but not in the 3CSRT task. Our data suggest that acute stressor exposure prior to testing does not impair cognitive performance in APPswe/PS1dE9 mice.